A Potent Systemically Active N-Acylethanolamine Acid Amidase Inhibitor that Suppresses Inflammation and Human Macrophage Activation - Ribeiro, Alison (ACS Chem Biol, 2015)
Fatty acid ethanolamides such as palmitoylethanolamide (PEA) and oleoylethanolamide (OEA) are lipid-derived mediators that potently inhibit pain and inflammation by ligating type-α peroxisome proliferator-activated receptors (PPAR-α). These bioactive substances are preferentially degraded by the cysteine hydrolase, N-acylethanolamine acid amidase (NAAA), which is highly expressed in macrophages. Here we describe a new class of β-lactam derivatives that are potent, selective and systemically active inhibitors of intracellular NAAA activity. The prototype of this class deactivates NAAA by covalently binding the enzyme's catalytic cysteine, and exerts profound anti-inflammatory effects in both mouse models and human macrophages. This agent may be used to probe the functions of NAAA in health and disease and as a starting point to discover better anti-inflammatory drugs.